Passiflora creuci-caetanoae a new species of Passiflora L. supersection Tacsonia (Passifloraceae) from Colombia - Bonilla Morales, Miguel Macgayver; Aguirre-Morales, Carolina; Cardenas, Julian (Phytotaxa, 2016)
A new species of Passiflora from the Andes of Cundinamarca and Meta regions (Colombian Eastern Cordillera) is described and illustrated. P. creuci-caetanoae is morphologically similar to the species of the section Colombianae ser. Colombianae, in particular with P. cuatrecasasii and P. adulterina. P. creuci-caetanoae is characterized by its straight trichomes, ovate-lanceolate leaves with truncate base, ensiform stipules and obovate petals. In addition, an improved key to section Colombiana ser. Colombiane for Colombia is provided, and information about ecology, distribution, and conservation status of P. creuci-caetanoae are discussed.